Change Management in Indonesian Higher Education: Systematic Analysis Based on Literature Review - Muda, Florianus Pruda (Journal of Social Science Utilizing Technology, 2024)
Background. This research study was conducted to identify, review and evaluate change management carried out in higher education institutions in Indonesia, with a focus on the positive impact from the perspective of academics, students and the general public. Purpose. The main aim of this research is to identify, review and evaluate change management carried out in higher education institutions in Indonesia. Method. The methodology in this research uses Systematic Literature Review (SLR) on journals indexed by Google Scholar over the last 10 years. Results. The research results show that changes, such as curriculum restructuring, technology integration, and adaptation to global challenges, have had a positive or positive impact on academics, students and society in general. More than student readiness to face global challenges, strengthening relationships with industry, and improving the quality of academic services are concrete results from implementing change management. Therefore, the implementation of effective change management strategies, responsive curriculum development, close collaboration between universities, industry and society, as well as adaptation to developments in educational technology are expected to increase the positive contribution of universities to education, students and society. Conclusion. Research shows that changes in Indonesian higher education have a significant positive impact, especially in improving academic quality. Implementation of change management, such as the Lewin and Robbins model, brings measurable results in the educational structure. Changes in learning methods, curricula, and technology integration increase the relevance of graduates in the job market.